2018 14th International Conference on Intelligent Environments (IE) 2018
DOI: 10.1109/ie.2018.00013
|View full text |Cite
|
Sign up to set email alerts
|

Context Feature Learning through Deep Learning for Adaptive Context-Aware Decision Making in the Home

Abstract: In Intelligent Environments, prediction and decision must take the context of interaction into account to adapt themselves to the evolving environment. If most of the approaches to deal with this problem have used a formal representation of context, we present in this paper a direct extraction of the context from raw sensor data using deep neural network and reinforcement learning. Experiments undertaken in a voice controlled smart home showed which elements are useful to perform context-aware decision-making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The study case concluded that the control response time was decreased with 6.98 ms compared to other architectures, while the precision was kept at 95.14%. On the other hand, two works to enhance comfort and home automation based on voice control are presented in [91], [92]. They use different classification algorithms of context data.…”
Section: Urban Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…The study case concluded that the control response time was decreased with 6.98 ms compared to other architectures, while the precision was kept at 95.14%. On the other hand, two works to enhance comfort and home automation based on voice control are presented in [91], [92]. They use different classification algorithms of context data.…”
Section: Urban Planningmentioning
confidence: 99%
“…The decisive context information is defined as activity, time and location after the processing of acquired data (speech, water consumption, lamp status, temperature and human presence sensor). In contrast, the application from [92] employs Deep Q Network (DQN) for context inference, any time the environment context changes. Thus, a graphical representation projects data on a two-dimensional map of the smart-home, integrating the context data from many heterogeneous sensors (e.g., temperature, contact-door and speech) into a unique image.…”
Section: Urban Planningmentioning
confidence: 99%
“…The activity recognition with deep learning becomes a hot topic recently (e.g., Wang et al [14] and Brenon et al [15]). Although the deep learning is a powerful approach to recognize image data, a huge amount of data is required to build a high-quality model.…”
Section: Related Workmentioning
confidence: 99%
“…One may try to recognize home contexts via image recognition based on deep learning. However, constructing a custom recognition model dedicated for a single house requires a huge amount of labeled datasets and computing resources [14,15]. Thus, there is still a big gap between the research and real life.…”
Section: Introductionmentioning
confidence: 99%
“…For this, one may try to recognize home contexts via image recognition based on naive deep learning. However, constructing a custom recognition model dedicated to a single house requires a huge amount of labeled datasets and computing resources [17,18]. It is not only hard to construct a universal recognition model from one house to another, but also the security and privacy issues that come with a large amount of data influence acceptability for the users.…”
Section: Introductionmentioning
confidence: 99%